Experimental and Numerical Testing of Jaw Gripper Design Using The Mass Reduction Method of Onyx-Carbon Fiber Material at PT. Matahari Megah - Santoso, Yudha; Halim, Agus; Utama, Didi Widya; Raynaldo, Kevin (Fakultas Teknik Universitas Pancasila, 2024)
A robot arm is a robot component in the motion subsystem of a robot system to determine the position and orient the object so that the robot can perform certain tasks, such as picking and placing an object. To use it as a pick and place, a gripper shaped like a human finger, commonly called a jaw gripper, is required, which is used to hold, tighten, hold, and release an object. The shape of the jaw gripper is designed and made according to the shape of the workpiece to be grasped, which was created by PT Matahari Megah using the 3D-printing method for its customer. The jaw gripper that has been designed still needs to be developed to produce a more optimal jaw gripper design, such as by reducing the use of excessive filament without reducing quality and minimizing costs incurred. Therefore, a more optimized jaw gripper test tool was made with a material reduction method using the generative design process in Inventor software, and physical testing was carried out on the ability to grip and deflection, compared to the testing process using a test system that had been designed with a dial gauge measuring instrument. The results of the comparison between the Inventor software results and the simulation results do not exceed 10%, with the difference at a pressure of 2 bars of 7% and the difference at a pressure of 4.6/5 bars of 1.87%.